The Non-U.S. Bank Demand for U.S. Dollar Assets - Adrian, Tobias; Xie, Peichu (Washington, D.C. : International Monetary Fund, 2020)
The USD asset share of non-U.S. banks captures the demand for dollars by these investors. An instrumental variable strategy identifies a causal link from the USD asset share to the USD exchange rate. Cross-sectional asset pricing tests show that the USD asset share is a highly significant pricing factor for carry trade strategies. The USD asset share forecasts the dollar with economically large magnitude, high statistical significance, and large explanatory power, both in sample and out of sample, pointing towards time varying risk premia. It takes 2-5 years for exchange rate risk premia to normalize in response to demand shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet